Pengembangan E-Modul Berbantu Digital Software dalam Materi Bentuk Aljabar di Sekolah Menengah Pertama - Kariani, Siti Maula (Jurnal of Math Tadris, 2024)
This research aims to produce learning media in the form of E-Modules in algebra form material to simplify the student learning process. E-Modules provide information without time limits, so that interesting, effective, efficient and efficient learning is achieved. This type of research is research and development (R&D) based on the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this research were class VII students at SMP Negeri 5 Jonggat. This research data was obtained using observation, interview and questionnaire techniques. The result was a field trial which was attended by 25 class VII A students who got a very interesting category with an average score of 3.53 and 25 class VIIB students got a very interesting assessment category with an average score of 3.5 out of 4.00 maximum score. With the conclusion that the e-module developed is suitable for use as a contemporary learning medium.